Implementing palliative care in hepatocellular carcinoma ambulatory clinics—study protocol for Accelerated translational research in PRImary liver CAncer (APRICA) randomised controlled palliative care trial - Gofton, Cameron; Di Bartolomeo, Anna; Boutros, Rose; Zurynski, Yvonne A.; Stafford-Bell, Fiona; Caldwell, Kim; McCaughan, Geoffrey; Zekry, Amany; Strasser, Simone I.; Levy, Miriam; Sheehan, Caitlin; Goodall, Stephen; et al. (Trials, 2024)
Integration of symptom and palliative care for people with advanced cancer is established in many tumour types, but its role in people with hepatocellular carcinoma (HCC) has not been clearly defined. This study aims to evaluate the clinical and cost effectiveness of an intervention involving a suite of strategies designed to assess and treat palliative care symptoms and needs in adult outpatients with HCC attending four New South Wales (NSW) metropolitan tertiary hospitals. This trial will use a pragmatic cluster-based randomised-controlled design, with ambulatory HCC services as the clusters. HCC patients will be recruited if they have Barcelona Clinical Liver Cancer (BCLC) stage A disease with active tumour or a current or prior diagnosis of BCLC stage B or C disease regardless of tumour activity. Patients with BCLC stage D disease will be excluded as palliative care is the standard of care (SOC) in this group. Cluster sites will be randomised to the study intervention or control where patients are managed according to SOC. All participants will complete the liver-specific Edmonton Symptom Assessment Scale (ESAS) and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire at regular ambulatory clinic appointments. At intervention sites, patients scoring ≥ 5 on any liver-specific ESAS symptom will be referred to palliative care physicians for consultation. The primary clinical outcome will be improvement in all symptoms scored ≥ 5 on the liver-specific ESAS by 50% within 3 months and the primary implementation outcome will recording the liver-specific ESAS in ≥ 80% of all participants attending clinic appointments. Caregivers of patients enrolled in the trial will be invited to perform Carer Support Needs Assessment Tool at each appointment. This trial will inform if earlier palliative care involvement significantly reduces the symptom burden associated with HCC. If found to be effective, earlier implementation of palliative care consultation should be included in HCC treatment guidelines. ACTRN12623000010695. Registered on September 1, 2023.